Integrating Khan Academy as Video-Based Instruction: A Pre Experimental Action Research on Grade 7 Learners’ Achievement and Engagement - Eric Lascoña; Douglas A Salazar (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This action research examined whether integrating Khan Academy video lessons into Grade 7 mathematics classes would improve learners’ achievement and engagement levels, and documented students’ perceptions of the videos after a two-week classroom intervention. Methodology: A pre-experimental one-group pretest–posttest design was employed. Research instruments included a researcher-made 30-item Mathematics achievement test validated by three in-service teachers (reliability = 0.7742), a Mathematics Engagement Level Questionnaire using a 5-point Likert scale (Cronbach’s α = 0.857), and purposively selected Khan Academy video lessons. Data were analyzed using the Wilcoxon Signed-Rank Test, Spearman’s rho, and thematic analysis. Main Findings: Post-intervention achievement increased significantly, rising from a mean of 10.42 to 17.62, although most learners remained at the “Beginning” level. Engagement levels also improved after the intervention. The relationship between post-intervention achievement and engagement was weak and not statistically significant. Learners reported clearer understanding, increased enjoyment, and greater motivation, alongside some issues related to audio clarity and retention. Novelty/Originality of this study: This study contributes to educational research by demonstrating how short, teacher-guided integration of video-based instruction can simultaneously influence mathematics achievement and multidimensional learner engagement in secondary classrooms. By combining validated pre–post quantitative measures with learners’ thematic feedback, the study extends existing evidence on video-based learning by identifying both instructional benefits and implementation constraints (e.g., audio clarity, retention), thereby informing more effective and context-sensitive blending of video resources in mathematics instruction.